Histo-Pathological Study of Endometrial Biopsies in Patients With Abnormal Uterine Bleeding - Parajuli, Sharmila; Thapa, Binita (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Abnormal uterine bleeding is a common sign of a number of different uterine disorders ranging from dysfunctional (non organic) abnormalities or complications of pregnancy to organic lesions such as polyps, hyperplasia or carcinoma. Methods: This is a retrospective study conducted at Hospital of 2nd author during a period of 5 years (Jan 2008-Dec 2013). Histopathology records were retrieved and searched for cases of abnormal uterine bleeding. Relevant histopathological findings and clinical data were recorded and analyzed. The aim of the study was to determine the causes for abnormal uterine bleeding in women presenting to the hospital and to compare the histopathological findings at various age groups. Results: The age of patients ranged from 17 to 71 years with an average of 43 years. The most common cause of uterine bleeding was found to be proliferative phase endometrium; that were 649 cases (56.43%). Out of the pathological causes, the most common cause was found to be endometrial hyperplasia- 44 cases (3.82%). Endometrial carcinoma was found to be more common in the elderly postmenopausal women. A total of 6 cases (0.5%) of endometrial carcinoma were present. Conclusion: Endometrial hyperplasias and malignancies are common in increasing age group, especially in perimenopausal and postmenopausal women. So, a thorough work-up and diagnostic endometrial biopsy is therefore mandatory without delay in these patients to rule out malignancies.